STRATEGI REGULASI EMOSI DAN PERILAKU KOPING RELIGIUS NARAPIDANA WANITA DALAM MASA PEMBINAAN Studi Kasus: Lembaga Pemasyarakatan Wanita Klas II A Bulu Semarang - Erlina Anggraini (Fakultas Ushuluddin dan Humaniora, Universitas Islam Negeri Walisongo Semarang, Indonesia, 2015)
Abstract: This article aims to elaborate emotion regulation strategies and religious coping of inmates in Clas II A women’s prison of Bulu Semarang. Staying at detention center or prison definitely makes someone stress and automatically influences to their social life, health-physics, and psychic. Moreover for new inmates (unrecidivist), the effect can be worse. The new athmosphere of the jail can make them feel meaningless, useless, bore, and give up. It means they get both of physics and psychology punishment. Therefore the inmates should be able to control their emotion and be adaptive in their ‘new live’. This ability is called emotion regulation. Surely, the good ability will help them to face many kinds of stressors in their life. This study describes emotion regulation strategies and religious coping of women inmates. because as known in most of the society, the women are more sensitive than the men. The method of this research is qualitative. The Informants of this study are inmates of Clas II A women’s prison of Bulu Semarang which taken by random system. The researcher finds that the inmates will be easier to face stressors if they have good-emotion regulation. such as having positive thinking and controlling their attitude and feeling. But if they con not regulate their emotion well, they will be easy to feel anxiety, depression and distress. They are also will be more more aggresive. Abstrak: Artikel ini bertujuan untuk mengelaborai strategi regulasi emosi dan koping religius narapidana wanita dalam masa pembinaan. Hidup dalam rutan, penjara atau lembaga pemasyarakatan (Lapas) pasti menimbulkan berbagai tekanan yang akan berdampak pada kehidupan sosial, keadaan fisik dan juga psikis narapidana, apalagi bagi narapidana baru (bukan residivis). Dampak fisik dan psikologis yang dialami oleh narapidana dapat membuat mereka merasa tidak bermakna (meaningless) yang ditandai dengan perasaan hampa, gersang, bosan, dan putus asa. Konflik batin seperti perasaan sedih, menyesal, khawatir, tertekan, merasa terbatasi, rindu keluarga, jenuh dan perasaan tidak mengenakkan lainnya muncul dalam diri mereka. Ini artinya bagi sebagian besar narapidana, penjara bukan saja hukuman fisik (serba terbatas) melainkan juga hukuman psikologis. Untuk itu narapidana harus memiliki kemampuan untuk bisa mengontrol emosi mereka agar tetap efektif dan adaptif dalam tekanan, kemampuan ini disebut regulasi emosi. Kemampuan regulasi emosi yang baik tentu akan sangat membantu narapidana dalam menghadapi masa-masa yang sulit dan penuh tekanan dalam masa pembinaan. Keywords: coping religious, narapidana, stressor, hukuman psikologis, hukuman fisik.